EU cultural action in the Southern Neighbourhood Policy: the development of a national cultural strategy in Jordan - Bouquerel, Fanny (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2018)
Med Culture (2014–2019), the European Union (EU) regional program dedicated to culture in Southern Mediterranean countries, aims at "supporting culture as a vector of democratization and development," and encouraging reforms in cultural policies. Responding to the desire of Jordan’s Ministry of Culture to develop a national cultural strategy, the Med Culture Technical Assistance Unit suggested implementing a process that included a series of consultations that would bring together authorities and independent cultural players. Through a thick description of the process and an approach that focuses on the sociology of the actors, this paper aims to identify the social effects of this European program on relations between the different stakeholders involved.